Analisis Strategi Manajemen Operasional pada Tadika Al-Fikh Orchard Pendamar Indah 2 Malaysia - Syehnaz Sahin Shiddiqi; Uswah Hasanah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research study investigates the pivotal function of strategy, operational management, and human resource management in the context of Tadika Al-Fikh Orchard Pendamar Indah 2, Malaysia.The objective of this research is to ascertain the interrelationships among these components and their practical ramifications for enhancing efficiency and effectiveness in business.Utilising a qualitative approach, data was collected through interviews and document analysis to ensure a comprehensive understanding of prevailing management practices. The findings indicate that an integrated strategy that aligns operational and human resource management enhances the resilience of institutions and fosters competitive advantage. These results suggest that organisations should prioritise strategic alignment to ensure dynamic survival and facilitate further research in developing adaptive management frameworks.